Computational docking-based investigation of Garcinia mangostana bioactive compounds as H1N1 influenza A virus neuraminidase - Azhar, Muhammad Daniel Amani; Abdullah, Mohamad Zakkirun; Bakar, Latifah Munirah (Faculty of Applied Sciences, Universiti Teknologi MARA, Shah Alam, Malaysia, 2025)
The H1N1 influenza virus, responsible for global pandemics, remains a significant public health challenge due to its high transmissibility and frequent mutations that render many antiviral drugs less effective. Current treatments, such as neuraminidase inhibitors, face limitations including drug resistance and adverse side effects. Garcinia mangostana (mangosteen), a tropical fruit traditionally valued for its medicinal properties, contains bioactive compounds with potential antiviral, antioxidant, and anti-inflammatory activities. This study explores the molecular docking of G. mangostana phytochemicals to identify potent inhibitors of the H1N1 neuraminidase enzyme, aiming to provide a foundation for the development of safer, plant-based antiviral therapies.